Research on Medical Education Reform in the Context of Educational Reform - Song, Guanglu; Askar, Madina; Gu, Yueju (Journal of Educational Research and Policies, 2026)
This paper systematically explores the pathways for integrating medical education from three dimensions: developmental patterns, value shaping, and learning methods. It proposes that medical education should integrate internal motivation with external guidance, embedding the core value of “health entrusted, life committed” throughout the entire process. In the digital era, it advocates balancing technological empowerment with the essence of education, fostering excellent medical talents who possess both sophisticated skills, humanistic warmth, and contemporary competence through internal and external synergy and the unity of knowledge and practice.